Reinforced Hyaluronic Acid‐Based Matrices Promote 3D Neuronal Network Formation. Issue 21 (1st September 2022) - Janzen, Dieter; Bakirci, Ezgi; Faber, Jessica; Andrade Mier, Mateo; Hauptstein, Julia; Pal, Arindam; Forster, Leonard; Hazur, Jonas; Boccaccini, Aldo R.; Detsch, Rainer; Teßmar, Jörg; Budday, Silvia; et al.
Abstract: 3D neuronal cultures attempt to better replicate the in vivo environment to study neurological/neurodegenerative diseases compared to 2D models. A challenge to establish 3D neuron culture models is the low elastic modulus (30–500 Pa) of the native brain. Here, an ultra‐soft matrix based on thiolated hyaluronic acid (HA‐SH) reinforced with a microfiber frame is formulated and used. Hyaluronic acid represents an essential component of the brain extracellular matrix (ECM). Box‐shaped frames with a microfiber spacing of 200 µm composed of 10‐layers of poly(ɛ‐caprolactone) (PCL) microfibers (9.7 ± 0.2 µm) made via melt electrowriting (MEW) are used to reinforce the HA‐SH matrix which has an elastic modulus of 95 Pa. The neuronal viability is low in pure HA‐SH matrix, however, when astrocytes are pre‐seeded below this reinforced construct, they significantly support neuronal survival, network formation quantified by neurite length, and neuronal firing shown by Ca 2+ imaging. The astrocyte‐seeded HA‐SH matrix is able to match the neuronal viability to the level of Matrigel, a gold standard matrix for neuronal culture for over two decades. Thus, this 3D MEW frame reinforced HA‐SH composite with neurons and astrocytes constitutes a reliable and reproducible system to further study brain diseases. Abstract : A reliable matrix formulation based on ultra‐soft thiolated hyaluronic acid (HA‐SH) reinforced by box‐shaped microfiber frames allows to setup 3D cell culture models suitable to investigate brain disease pathologies. Combined microfiber frames and HA‐SH prevent the HA‐SH from losing its form stability and drying out. Astrocytes represent essential physiological key players required for neuronal maturation and network firing activity.